First term = T(1) is obtained by plugging n = 1 into the formula,
thus First term = 1^2 - 4 = 1 - 4
= 3 (answer)
[see picture link]Area of part 1:A1=base*height/2=(8+2)*(8-2-2-1)/2=10*3/2=15 ft^2Area of part 2:A2=length*width=(8+2)*1=10 ft2Area of part 3:A3=length*width=8*2=16 ft2
Picture: https://us-static.z-dn.net/files/d30/9033549987fa60cf57fe05f71424f322.gif
Answer:4
Step-by-step explanation:
Answer:
y= -7 and x= -1
Step-by-step explanation:
To do this, line up the variables so it looks like this...
y-6x=-1
y-3x=-4
The reason why -6x and -3y changes to negative is because that it moved to the other side of the equation.
distribute negative to the bottom equation because the two equations have the same number variable which is y...
y-6x=-1
-y+3x=4
Y cancels out and it will be left with -3x = 3.
X = -1.... plug that in to any of the two equation and you get y = -7.
Hope I helped and have a nice day!!
To solve any equation, you do whatever you need to do
to wind up with the unknown quantity all alone on one side.
BUT ... whatever you do to one side of the equation, you must
also do to the other side.
Here, we have the
he original equation: -15 = a/5
Multiply each side by 5 : -75 = a
and bada-bing, THERE's the solution !